DAMPAK REFORMASI PENDIDIKAN INDONESIA DI ABAD 21 - Epi Supriyani Siregar (Universitas Negeri Medan, 2021)
Abstract: The Impact of Educational Reform in the 21st Century. The ongoing educational reform is to restore the role of education because everyone should not miss episodes of the education system that can elevate the high and noble dignity of life. With the will of various parties will certainly be able to realize the ideals and hopes of human life. Those expectations include; In politics, reform, which is believed to be rolling in the desired direction, not only stops reform but also continues these ideals and hopes. To advance the concept of education in Indonesia, several changes must be made, such as: 1) revamping the concept of conventional education; 2) Understanding education as an important part of efforts to create change for the better management of the life of the nation and state; 3) Creating education that can adapt to the changing nature of globalization; 4) Responding positively to the current globalization changes and then directing them to the concept of sustainable management, and 5) Creating the concept of sustainable education. Keywords: Reform, Education Abstrak: Dampak Reformasi Pendidikan di Abad 21. Reformasi pendidikan yang sedang berlangsung adalah mengembalikan peran pendidikan karena setiap orang tidak boleh melewatkan episode-episode sistem pendidikan yang dapat mengangkat harkat dan martabat kehidupan yang tinggi dan agung. Dengan kemauan berbagai pihak tentunya akan mampu mewujudkan cita-cita dan harapan hidup manusia. Harapan itu meliputi; politik, reformasi, yang diyakini akan bergulir ke arah yang diinginkan, tidak hanya menghentikan reformasi tetapi juga melanjutkan cita-cita dan harapan tersebut. Untuk memajukan konsep pendidikan di Indonesia, beberapa perubahan harus dilakukan, seperti: 1) pembenahan konsep pendidikan konvensional; 2) Memahami pendidikan sebagai bagian penting dari upaya menciptakan perubahan untuk pengelolaan kehidupan berbangsa dan bernegara yang lebih baik; 3) Menciptakan pendidikan yang dapat menyesuaikan dengan perubahan sifat globalisasi; 4) Merespon perubahan globalisasi yang terjadi saat ini secara positif dan selanjutnya mengarahkannya pada konsep pengelolaan berkelanjutan (sustainability management), dan 5) Menciptakan konsep pendidikan berkelanjutan. Kata Kunci: Reformasi, Pendidikan